Do associations between objectively-assessed physical activity and neighbourhood environment attributes vary by time of the day and day of the week? IPEN adult study - Cerin, Ester; Mitáš, Josef; Cain, Kelli L; Conway, Terry L; Adams, Marc A; Schofield, Grant; Sarmiento, Olga L; Reis, Rodrigo Siqueira; Schipperijn, Jasper; Davey, Rachel; Salvo, Deborah; Orzanco-Garralda, Rosario; et al. (The international journal of behavioral nutrition and physical activity, 2017)
BACKGROUND: To more accurately quantify the potential impact of the neighbourhood environment on adults' physical activity (PA), it is important to compare environment-PA associations between periods of the day or week when adults are more versus less likely to be in their neighbourhood and utilise its PA resources. We examined whether, among adults from 10 countries, associations between objectively-assessed neighbourhood environment attributes and moderate-to-vigorous physical activity (MVPA) varied by time of the day and day of the week. The secondary aim was to examine whether such associations varied by employment status, gender and city. METHODS: This cross-sectional study included 6,712 adults from 14 cities across 10 countries with ≥1 day of valid accelerometer-assessed MVPA and complete information on socio-demographic and objectively-assessed environmental characteristics within 0.5 and 1 km street-network buffers around the home. Accelerometer measures (MVPA min/h) were created for six time periods from early morning until late evening/night, for weekdays and weekend days separately. Associations were estimated using generalized additive mixed models. RESULTS: Time of the day, day of week, gender and employment status were significant moderators of environment-MVPA associations. Land use mix was positively associated with MVPA in women who were employed and in men irrespective of their employment status. The positive associations between MVPA and net residential density, intersection density and land use mix were stronger in the mornings of weekdays and the afternoon/evening periods of both weekdays and weekend days. Associations between number of parks and MVPA were stronger in the mornings and afternoon/evenings irrespective of day of the week. Public transport density showed consistent positive associations with MVPA during weekends, while stronger effects on weekdays were observed in the morning and early evenings. CONCLUSIONS: This study suggests that space and time constraints in adults' daily activities are important factors that determine the impact of neighbourhood attributes on PA. Consideration of time-specific associations is important to better characterise the magnitude of the effects of the neighbourhood environment on PA. Future research will need to examine the contribution of built environment characteristics of areas surrounding other types of daily life centres (e.g., workplaces) to explaining adults' PA at specific times of the day.
Keywords: Young Adult; Cross-Sectional Studies; velkoměsta; Male; periodicita; mladý dospělý; Adolescent; Adult; rozložení podle pohlaví; akcelerometrie; Aged; dospělí; mužské pohlaví; senioři; Periodicity; Employment; Exercise; reprodukovatelnost výsledků; Sex Distribution; Reproducibility of Results; mladiství; Residence Characteristics; Time; lidé; Cities; Environment Design; ženské pohlaví; Humans; čas; průřezové studie; zaměstnanost; Accelerometry; Female; cvičení; lidé středního věku; životní prostředí - projekt; charakteristiky bydlení; Middle Aged